2018
DOI: 10.1093/gigascience/giy140
|View full text |Cite
|
Sign up to set email alerts
|

NanoAmpli-Seq: a workflow for amplicon sequencing for mixed microbial communities on the nanopore sequencing platform

Abstract: BackgroundAmplicon sequencing on Illumina sequencing platforms leverages their deep sequencing and multiplexing capacity but is limited in genetic resolution due to short read lengths. While Oxford Nanopore or Pacific Biosciences sequencing platforms overcome this limitation, their application has been limited due to higher error rates or lower data output.ResultsIn this study, we introduce an amplicon sequencing workflow, i.e., NanoAmpli-Seq, that builds on the intramolecular-ligated nanopore consensus sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 41 publications
2
57
0
1
Order By: Relevance
“…PacBio HiFi sequencing mode produces highly accurate reads using their circular consensus sequencing (CCS) technology, reducing raw read error to < 1% (Wenger et al 2019). Similarly, rolling circle amplification can be used in metabarcoding applications to mitigate error rates of the nanopore-based sequencing platforms (Calus et al 2018).…”
Section: Environmental Dna Metabarcoding Of Spidersmentioning
confidence: 99%
“…PacBio HiFi sequencing mode produces highly accurate reads using their circular consensus sequencing (CCS) technology, reducing raw read error to < 1% (Wenger et al 2019). Similarly, rolling circle amplification can be used in metabarcoding applications to mitigate error rates of the nanopore-based sequencing platforms (Calus et al 2018).…”
Section: Environmental Dna Metabarcoding Of Spidersmentioning
confidence: 99%
“…Our HTS data are based on the pyrosequencing 454 method (Roche) that has been replaced by newer platforms that provide sequencing depth orders of magnitude higher, such as Illumina or Oxford Nanopore. However, as the main biases arise from DNA extraction, PCR amplification, and uneven 16S and 18S rRNA gene copy numbers (47), these newer methods will not necessarily improve the quantitative accuracy of the sequencing data, as shown with mock communities sequenced using Illumina (13)(14)(15) and Oxford Nanopore (48,49) platforms. In contrast, the relative abundances of sequences obtained from the same samples by both pyrosequencing and Illumina correlated very strongly (r 2 ÏŸ 0.99) (50).…”
mentioning
confidence: 99%
“…This technology allows the sequencing of the full-16S rRNA gene, increasing the capacity for taxonomical assignation, and it can be performed in real-time with reduced equipment, increasing its potential as a field tool for remote locations 23 . However, despite these advantages, when comparing to short reads sequencing such as Illumina, the error rate is higher 22 , problem that has been progressively mitigated with technological advances and better bioinformatic tools 24,25 . Regarding the study of microbiota, several studies have been dedicated to compare taxonomical analysis derived by this technology with Illumina sequencing, and have shown that error rate has been compensated with larger fragments, providing in some cases higher taxonomical resolution 26,27 .…”
mentioning
confidence: 99%